Nucleotide sequence of the osmoregulatory proU operon of Escherichia coli. - Gowrishankar, J (1989)
The sequence of 4,362 nucleotides encompassing the proU operon of Escherichia coli was determined. Three open reading frames were identified whose orientation, order, location, and sizes were in close accord with genetic evidence for three cistrons (proV, proW, and proX) in this operon. Similarities in primary structure were observed between (i) the deduced sequence of ProV with membrane-associated components of other binding-protein-dependent transport systems, in the nucleotide-binding region of each of the latter proteins, and (ii) that of ProW with integral membrane components of the transport systems above. The DNA sequence data also conclusively established that ProX represents the periplasmic glycine betaine-binding protein. Two copies of repetitive extragenic palindromic sequences were identified beyond the 3' end of the proX gene. The primer extension technique was used to identify the 5' ends of proU mRNA species that are present in cells grown at high osmolarity; the results suggest that at least some of the osmotically induced proU transcripts have a long leader region, extending as much as 250 base pairs upstream of the proV gene. Evidence was also obtained for the existence of a sequence-directed bend in DNA in the upstream regulatory region of the proU operon.